Gaya Seni Relief Yeh Pulu di Kabupaten Gianyar, Bali - Kadek Dedy Prawirajaya Rajeg; Heri Purwanto (Pusat Penelitian Arkeologi Nasional, 2021)
The relationship between Indonesia and India manifested in various cultural forms that still survive today, one of which is in form of relief. Yeh Pulu is an archaeological site located in Banjar Batulumbang, Bedulu Village, Blahbatuh District, Gianyar Regency, Bali. To date, the relief in Yeh Pulu has not been studied intensely. The objective of this research is to reveal the characteristics of reliefs in Yeh Pulu Site. Data collection was carried out through direct observations in the field and also photographs. A comparative study was used for the analysis, by comparing Yeh Pulu Relief with the reliefs from temples in Java. The results showed that the Yeh Pulu Relief has nine scenes depicting various activities of past lives. One of the scenes depicted the story of Kresnayana, which perhaps was the inspiration for the reliefs. Yeh Pulu relief was developed around 14 – 15 AD or during late Majapahit era.